Research on the Current Situation and Countermeasures of Young Pioneers’ Organizational Citizenship Behavior - Zheng, Fengqiong (Journal of Theory and Practice in Education and Innovation, 2024)
In order to understand the current situation and influencing factors of Organizational citizenship behavior (OCB), explore the relationship between organization justice, organization identity (OI) and OCB, so as to better carry out the education of young pioneers. This study adopts OCBS, OJS and the OIS of elementary school 3-6 grade 1200 young pioneers to carry out the survey, statistical analysis, the data found that the young pioneers’ organization justice, OI and and OCB in grade, whether as a student cadres differences, the young pioneers OJ, OI and OCB between the positive correlation, OI working as an intermediary variable between OJ and OCB relationship between some intermediary role. Based on the analysis of research results, this paper proposes some strategies to improve the work of young pioneers.